Arrangement of Herpesvirus Deoxyribonucleic Acid in the Core - Furlong, D. (1972)
The core of the herpes simplex virion consists of an electron-dense toroidal structure 50 nm high, with an inside diameter of 18 nm and an outside diameter of 70 nm, penetrated by a less dense cylindrical mass. The toroid contains deoxyribonucleic acid (DNA), as evident from the observation that uranyl ion staining is removed by ethylenediaminetetraacetic acid under conditions which result in the extraction of uranyl ions bound to nuclear DNA. Studies on negatively stained preparations of purified capsids suggest that the toroid consists of DNA arranged as if it were spooled around the cylindrical mass.